Inter-and intra-annual variability in meiofaunal community structure in a seagrass site affected by an oil spill in Southern Guimaras, Philippines - Burgos, Lorelie A. (University of the Philippines-Visayas, 2013)
This study was conducted to determine the inter- and intra-annual variabilty of meiofaunal community in the Calaparan seagrass bed affected by oil spill in Southern Guimaras. Inter-annual samples were taken yearly from 2005 to 2010. Intra-annual variability samples on the other hand were collected quarterly in May 2011, August 2011 and February 2012., A total of 53 meiofaunal taxa was identified, dominated by nematodes followed by copepods largely comprised of harpacticiods. The overall mean density of meiofauna in the Calaparan seagrass bed in Southern, Guimaras was 22.0 ind. cm -2. Highest density was recorded in September 2007 while lowest density was recorded in october 2009. The meifaunal distribution showed distinct inter-and intra-annual variability. Meiofaunal community was affected by both natural (typhoon Frank) and anthropogenic (oil spill) disturbances. Both type of disturbances decreased meiofaunal densities and altered species composition. Intra-annual meiofaunal distribution revealed highest abundance and lowest diversity during southwest monsoon (Aug. 2011). Meiofaunal seasonality pattern was affected by changes in abiotic factors (salinity & temperature), enhanced food sources due nutrient run-off from the land and sediment resuspension an dphysical disturbance brought by frequent storms during southwest monsoon. Spatial variation in meiofaunal assemblage between transect was primarily influenced by seagrass cover and sediment characteristics.